Kajian Tiny House Berdasarkan Simulasi Ruang Gerak Secara Antropometri di Indonesia - Lilian Putri Litaay; James ED Rialtupa; Aryantono Martowardjoyo (Arsir: Jurnal Arsitektur, 2024)
Tiny houses generally emphasise more on design balance than size, users will prefer to use multifunctional furniture to minimise the use of a lot of furniture and optimize space (Pratiwi, 2023). The small size makes room divisions made as efficient as possible but sufficient for the needs of residents. So this research was conducted to find anthropometric movement systems of Indonesians against tiny houses.In this study, measurement data from research objects were simulated through the identification of space functions, furniture and activities in it.Then described in the form of layouts by displaying space patterns and functions. The population living in the 3(three) types of tiny houses located in 3(three) different areas in Bali. Simulation is done using computers and software in the form of Sketch Up. From the results of the study, it can be seen that tiny houses with thoughtful design can turn even the smallest space into a functional and comfortable living environment. The room looks bigger and multifunctional when combined. The use of minimalist furniture also affects the design of the existing room, where the right selection makes a broad impression, but otherwise the room can seem cramped.